Patient and physician factors contributing to polypharmacy among older patients. (2nd January 2022) - Martinez, Kathryn A.; Linfield, Debra T.; Gupta, Niyati M.; Alapati, Mohana Vamsi; Moussa, Daniel; Hu, Bo; Kim, Luke Dogyun; Lam, Simon; Russo-Alvarez, Giavanna; Rothberg, Michael B.
Abstract: Objective: Polypharmacy, or use of multiple medications, is associated with patient factors. Less is known regarding variation in polypharmacy by individual physicians. The objective of this study was to assess patient and physician factors associated with polypharmacy among older patients. Methods: This is a cross-sectional study of patients aged ≥65 years with a primary care visit at Cleveland Clinic Health System in 2015 and their physicians. We collected patient demographics, comorbidities and current medications from the electronic health record, including potentially inappropriate medications (PIMs). We used mixed effects linear regression to estimate adjusted differences in the number of medications by patient factors. We generated adjusted prescribing rates for individual physicians and assessed differences in physician performance on quality measures by their prescribing rate. Results: Our study included 44, 570 patients who were prescribed an average of 6.8 medications (standard deviation: 4.0) by 701 physicians. Female sex, higher BMI, having Medicaid insurance, current or former smoking status, comorbidities and seeing a specialist were associated with number of medications. Age was not. Among 267 physicians who saw ≥20 study-eligible patients, the adjusted mean number of medications per patient ranged from 5.2 to 9.6. Compared to physicians who prescribed above the mean, lower prescribing physicians performed significantly better on medication reconciliation ( p = .007) and hypertension control ( p < .001) and prescribed fewer PIMs ( p < .001). Conclusions: Individual physicians varied in their prescribing practices, even after adjusting for patient demographic and clinical characteristics. Interventions to reduce polypharmacy in older adults should target high prescribing physicians, as physician behavior is more actionable than patient factors.